PENGARUH SUBJECTIVE WELL-BEING DAN PSYCHOLOGICAL CAPITAL TERHADAP KINERJA PEGAWAI PEMERINTAH DAERAH KABUPATEN MOROWALI - Tovan Tovan; Rusdiaman Rauf (Jurnal Mirai Management, 2020)
The purpose of this study was to determine the simultaneous and partial effect of subjective well-being and psychological capital on the performance of the Morowali Government employees. The type of research used is quantitative and the sampling technique used in this study is proportional random sampling with a total sample of 120 respondents. The results of this study found that subjective well-being and psychological capital simultaneously and partially had a significant effect on the performance of the Morowali Government employees. Keywords: Subjective Well-being, Psychological Capital and Employee Performance